Culture, society, and development in India : essays for Amiya Kumar Bagchi - Bagchi, Amiya Kumar; Sanyal, Manoj Kumar; Ghosh, Arunabha (New Delhi : Orient BlackSwan, 2009)
Festschrift on Amiya Kumar Bagchi, b. 1936, Indian economist and historian; contributed articles.
section 1. Language, culture and the Indian middle class : the development dilemma -- section 2. Women in real life, utopias and fictions -- section 3. Music and art : past and present -- section 4. Popular Indian cinema : ideology, culture and business.
Includes bibliographical references p. 168-176.
Keywords: Cultural pluralism -- India; Multilingualism -- India; Bengali language -- Social aspects; Language and culture -- India; Women in motion pictures; Women in literature; Motion pictures -- Social aspects -- India; Popular culture -- India